Earsplitters! : the world's loudest noises - Parker, Steve, 1952- (Mankato, Minn. : Capstone Press, 2008)
Presents the science behind sound including dragster races, rock concerts, and rockets.
Includes bibliographical references (p. 31), filmography, and index.
Book Links (A.L.A.).
Book Links (A.L.A.), June 2010.
4.8
3-6
Keywords: Noise -- Juvenile literature; Sounds -- Juvenile literature; Noise; Sounds; Noise; Sounds